(untitled) (Research, Society and Development, 2022)
Objective: Analyze what is understood as causes for myocardial injuries in those affected by SARS-CoV-2, investigating how much this occurrence has the capacity to impact in mortality and ascertain whether this cardiac injury has the potential to generate sequelae. Methodology: This systematic review was conducted according to the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-analyzes). Inclusion criteria included studies that analyze the causes, manifestations, and consequences of the interaction between COVID-19 and myocardium, published in the year 2020 and from January to March 2021 in the bibliographic databases Science Direct, LILACS, MEDLINE, Scielo and PUBMED. Results: After removing duplicates and screening abstracts, 22 articles were potentially eligible for inclusion in this review. After analyzing the texts in full, 16 were included in the research. Six are literature reviews, seven are retrospective studies, one is a case report, one is an experimental study and one is an observational study. Conclusions: Cardiac biomarkers provide fundamental data on the outcome of the disease, mainly because they are able to predict the risk of complications or death. Little is known to date as to whether those recovered from COVID-19 who have had myocardial damage will have relevant cardiac dysfunctions in the long run. More time and more research on the topic its needed.